Meta-Analysis of the Effect of Telemonitoring on Blood Sugar Levels and Quality of Life in Diabetes Patients - Sholihah, Anisa Asri; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Type 2 diabetes mellitus (DM), a chronic disease, requires continuous monitoring and treatment to have a better quality of life. Telemonitoring is a medium that may help in monitoring patients with type 2 DM. This study aimed to analyze the effect of using telemonitoring on blood sugar levels and quality of life of patients with type 2 DM with a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis conducted with PRISMA flow diagram. The articles were collected through journal databases, including PubMed, Google Scholar, Science Direct, and ProQuest, published in 2000-2021. The keywords used were (